Analisis pengaruh biaya kualitas dalam meningkatkan profitabilitas perusahaan PT. Putra Karangetang - Tambingon, Ridel; Karamoy, Herman; Pangerapan, Sonny (Indonesia Accounting Journal, 2020)
Measuring quality qualitatively gave rise to the term quality cost. Quality costs at PT. Putra Karangetang turned out to have a considerable influence on the profitability of the Company, where by allocating greater costs to control and valuation would reduce the costs of internal failure and the cost of external failure so that the impact on profit was increasing. The purpose of this study was to analyze the effect of quality costs in increasing profitability at PT. Putra Karangetang. The method used is descriptive qualitative method and using Return On Investment (ROI) as a measure of company profitability. ROI value is influenced by the company's net profit compared to the company's total assets, and the results of research prove that quality costs incurred to produce quality products, and the contribution of quality costs greatly affect the increase in profitability of the company.